The Approach of Daily Life Pedestrian Behavior for Urban Development in Hat Yai City - Ruthirako, Poonyanuch (Hatyai Academic Journal, 2020)
The aim of this paper is to study pedestrian behavior for urban development in Hat Yai City using quantitative and qualitative methods. The behaviors were codified following a standardized observation. The result showed that the first behavior was walking (58.5%). The frequency of walking was 23.5%, and the purpose was to go shopping (38.5%). The length of walks was less than 500 meters (23.5%) with less than 15 minutes spent (19.8%). The top three problems and obstacles were the feeling of insecurity (afraid of car crashes), parking on footpaths, and toxic pollution (dust and exhaust fumes). The smallest problem or obstacle was being insulted because of being poor. The approaches for developing pedestrians were adding lighting to pedestrian areas, adding crosswalks and traffic lights, providing sidewalks for the disabled and people in wheelchairs, providing pedestrian paths in some places where pedestrian paths are still deficient, providing ready-to-use pavilions for sidewalk shelters, and repairing the sidewalks which are damaged.